Instytucje a konkurencyjność rynku rolnego - Zalesko, Marian (Institutions and Competitiveness of Agricultural Market, 2006)
Well organized system of institutions is a very important factor influencing normal functioning of the agricultural market in Poland. The degree of institutionalization of agricultural market have particular significance after Poland's accession to the European Union. A comprehensive institutional system strengthens the economic position of Poland on the international market. In Poland institutions are weak what significantly reduces the competitiveness of Polish agriculture on the world market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 535-539